Can Adverse Effects of Acidity and Aluminum Toxicity Be Alleviated by Appropriate Rootstock Selection in Cucumber? - Rouphael, Youssef; Rea, Elvira; Cardarelli, Mariateresa; Bitterlich, Michael; Schwarz, Dietmar; Colla, Giuseppe (Frontiers in Plant Science, 2016)
Low-pH and aluminium (Al) stresses are the major constraints that limit crop yield in acidic soils. Grafting vegetable elite cultivars onto appropriate rootstocks may represent an effective tool to improve crop tolerance to acidity and Al toxicity. Two greenhouse hydroponic experiments were performed to evaluate growth, yield, biomass production, chlorophyll index, electrolyte leakage, mineral composition and assimilate partitioning in plant tissues of cucumber plants (Cucumis sativus L.‘Ekron’) either non-grafted or grafted onto ‘P360’ (Cucurbita maxima Duchesne × Cucurbita moschata Duchesne; E/C) or figleaf gourd (Cucurbita ficifolia Bouché; E/F). Cucumber plants were cultured in pots and supplied with nutrient solutions having different pH and Al concentrations: pH 6, pH 3.5, pH 3.5 + 1.5 mM Al and pH 3.5 + 3 mM Al (Exp. 1, 14 d) and pH 6, pH 3.5 and pH 3.5 +0.75 mM Al (Exp. 2, 67 d). Significant depression in shoot and root biomass was observed in response to acidity and Al concentrations, with Al-stress being more phytotoxic than low pH treatment. Significant decrease in yield, shoot and root biomass, leaf area, SPAD index, N, K, Ca, Mg, Mn, and B concentration in aerial parts (leaves and stems) in response to low pH with more detrimental effects at pH 3.5 + Al. Grafted E/C plants grown under low pH and Al had higher yield, shoot and root biomass compared to E/F and non-grafted plants. This better crop performance of E/C plants in response to Al stress was related to i) a reduced translocation of Al from roots to the shoot, ii) a better shoot and root nutritional status in K, Ca, Mg, Mn, and Zn concentration, iii) a higher chlorophyll synthesis, as well as iv) the ability to maintain cell membrane stability and integrity (lower electrolyte leakage). Data provide insight into the role of grafting on Al stress tolerance in cucumber.